2015
DOI: 10.1055/s-0034-1543976
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Local Intra-Arterial Nimodipine for the Treatment of Cerebral Vasospasm

Abstract: Vasospasm (VSP) is one of the major causes for prolonged neurologic deficit in patients with aneurysmal subarachnoid hemorrhage. Few case series have reported about continuous local intra-arterial nimodipine administration (CLINA) in refractory VSP. We report our experience with CLINA in a patient with refractory cerebral VSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…23 A clinical study in intensive care unit found that 23% of the patients had improvement of neurological deficits and 83% had good clinical condition and this therapy can be considered as a low risk of treatment for refractory vasospasm. 24,25 Local IA nimodipine is also a high safety procedure and gives improvement in vasospasm; nevertheless there are some limitations such as there are no guidelines about selection of patients, duration of treatment or dosage of nimodipine.…”
Section: B Nimodipinementioning
confidence: 99%
“…23 A clinical study in intensive care unit found that 23% of the patients had improvement of neurological deficits and 83% had good clinical condition and this therapy can be considered as a low risk of treatment for refractory vasospasm. 24,25 Local IA nimodipine is also a high safety procedure and gives improvement in vasospasm; nevertheless there are some limitations such as there are no guidelines about selection of patients, duration of treatment or dosage of nimodipine.…”
Section: B Nimodipinementioning
confidence: 99%